2024
DOI: 10.1186/s12888-023-05447-8
|View full text |Cite
|
Sign up to set email alerts
|

The patterns, trends and major risk factors of suicide among Indian adolescents – a scoping review

Rachel Elizabeth Senapati,
Susangita Jena,
Jayashree Parida
et al.

Abstract: Background Adolescence is an essential stage for the development of mental health, and suicide is among the leading cause of mortality for adolescents around the world. In India, the suicide rate among adolescents has been increasing in recent years. The scoping review was conducted to map the evidence and address gaps by examining the existing pattern, and trends, and identify the major risk factors of suicide among Indian adolescents. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In a study of Chinese university students, Chu et al ( 2021 ) found that higher levels of perceived social support were associated with lower levels of suicidal ideation with stress as the mediator. Modernity-driven changes in family structure, perception of being neglected or ignored by parents, excessive use of social media, a history of childhood trauma were often identified as suicide related risk factors (Kar, 2010 ; Bhosle et al, 2015 ; Senapati et al, 2024 ) in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Chinese university students, Chu et al ( 2021 ) found that higher levels of perceived social support were associated with lower levels of suicidal ideation with stress as the mediator. Modernity-driven changes in family structure, perception of being neglected or ignored by parents, excessive use of social media, a history of childhood trauma were often identified as suicide related risk factors (Kar, 2010 ; Bhosle et al, 2015 ; Senapati et al, 2024 ) in India.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has explored the interplay between emotional regulation, coping processes, and suicidal ideation (Jose and Angelina, 2020 ; Wastler and Núñez, 2022 ). A recently published article reviews and explains how the inability to cope with daily life stressors, the absence of peer group or family support, and not having kin around often have a debilitating effect on suicidal ideation (Senapati et al, 2024 ). At this standpoint our study aims to contribute to the existing literature by exploring the extent to which cognitive reappraisal and expressive suppression predict suicidal ideation while considering perceived social support and avoidant coping as potential mediating factors.…”
Section: Introductionmentioning
confidence: 99%